A revision of the genus Leberis Smirnov, 1989 (Cladocera: Chydoridae) in the Old World and Australia - Neretina, Anna N.; Sinev, Artem Y. (Zootaxa, 2016)
A comparison between populations of the diaphanus-group of Leberis Smirnov, 1989 from Australia and India confirmed that Australian L. diaphanus (King, 1853) and Indian L. punctatus (Daday, 1898) are separate species. Morphology of parthenogenetic females of L. punctatus is redescribed for the first time. Some fine details of morphology are re-examined in other species of Leberis, taxonomically significant features and their variability are studied. In the Old World L. punctatus could be confused with L. diaphanus, but the former differs from the latter mainly in the details of thoracic limbs I and IV. Both species have relatively broad distribution ranges: L. punctatus inhabits South Asia, Africa and penetrates Southeast Asia, L. diaphanus is a widespread taxon in the water bodies of Australia, Southeast Asia and South China. Diversity of the genus in the Old World is underestimated yet, and further investigations are desirable.